Changes in the gender pay gap over time: The case of West Germany - Marina Bonaccolto-Töpfer; Carolina Castagnetti; Luisa Rosti (Journal for Labour Market Research, 2023)
Using data from the German Socio-Economic Panel, this paper analyzes changes in the gender pay gap in West Germany between 1984 and 2020. The literature generally observes a catching-up of women over time with a slowdown since the mid-1990s and often concentrates on the USA. We present both an aggregate and detailed decomposition of changes in wages allowing us to directly test for changes in the components of the decomposition across gender and time. Apart from standard OLS, we use linear unconditional quantile regressions in order to be able to take changes in the gap and its components at the mean and across the distribution into account. We find that the gender pay gap statistically significantly declined at the bottom and the middle, while it increased at the top of the wage distribution. These results suggest that glass ceiling is a major challenge to the West German labour market.
Keywords: J7; J13; J31; 330; Changes in the gender pay gap; Decomposition; Unconditional quantile regression